2012
DOI: 10.1519/jsc.0b013e31823c4172
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Dropping Height on Jumping Performance in Trained and Untrained Prepubertal Boys and Girls

Abstract: Plyometric training in children, including different types of jumps, has become common practice during the last few years in different sports, although there is limited information about the adaptability of children with respect to different loads and the differences in performance between various jump types. The purpose of this study was to examine the effect of gender and training background on the optimal drop jump height of 9- to 11-year-old children. Sixty prepubertal (untrained and track and field athlet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
1
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 27 publications
2
27
1
2
Order By: Relevance
“…The DJ performance remained unchanged with incremental drop heights in the current study, which agreed with Bassa et al [40] and Bencke et al [41] but contrasted with Prieske et al [37], Andrade et al [38] and Lesinski et al [39]. Prieske et al [37] reported that both the DJH and RSI increased with drop heights from 20-to 50-cm and from 20-to 35-cm, respectively, in 239 adolescent handball players, irrespective of sex.…”
Section: Discussionsupporting
confidence: 90%
“…The DJ performance remained unchanged with incremental drop heights in the current study, which agreed with Bassa et al [40] and Bencke et al [41] but contrasted with Prieske et al [37], Andrade et al [38] and Lesinski et al [39]. Prieske et al [37] reported that both the DJH and RSI increased with drop heights from 20-to 50-cm and from 20-to 35-cm, respectively, in 239 adolescent handball players, irrespective of sex.…”
Section: Discussionsupporting
confidence: 90%
“…The above mentioned studies (Bobbert et al, 1987;Quatmant et al, 1987,Bassa et al 2012 cannot provide explanation for the obtained data regarding JG, because in the current study we used DH normalized to maximal squat jump heights while they did not. Possibly the non existence of JG could be explained on the peculiarities related with people with MI during jumping.…”
Section: Jpes ®mentioning
confidence: 68%
“…For example, Bobbert, Huijing, and van Ingen Schenau (1987) observed no JG when male adults performed drop jumping from 20, 40, and 60 cm. Furthermore, Quatman, Quatman, and Hewett, (2009) did not observe any JG when young female basketball players executed DJ from 15, 35 and 45 cm.No jumping gain was also observed in children jumping from 10 up to 50 cm (Bassa et al 2012). However, there is strong evidence and widely accepted that JG up to a certain DH level, increases and then it is stabilized in trained and untrained adults (Komi & Bosco, 1978;Voigt et al, 1995).…”
Section: Jpes ®mentioning
confidence: 98%
See 1 more Smart Citation
“…2004;Byrne et al 2010;Pietraszewski & Rutkowska-Kucharska 2011) али његова поузданост и потребан број понављања да би се добила висока поузданост у наведеним студијама није проверавана. У великом броју досадашњих истраживања DH opt је одређивана варијаблом H методом бирања (Komi & Bosco 1978;Viitasalo 1982;Bobbert et al 1987;Lees & Fahmi 1994;Voigt et al 1994;Viitasalo et al 1998;Bassa et al . 2012).…”
Section: предикција поузданости за одређивање оптималне висине саскокаunclassified